192k views
0 votes
Simplify. (-3)2 -32 -30

User Zverok
by
5.7k points

1 Answer

4 votes

We need to simplify the next given expression:


(-3)^2-3^2-3^0

Let's solve each term:


(-3)^2=(-3)(-3)=9
3^2=3\cdot3=9

Finally, for the last term we need to use the next property:


a^0=1

Every whole number with an exponent of 0 will always equal one.

Therefore:


3^0=1

Now, we have the next expression:


9-9-1
=-1

Hence, when we simplified the expression the result is -1.

User Neojakey
by
6.0k points